Polyolefin composition as well as preparation method and application thereof
By introducing ester comonomers and ester polymers during the polymerization process, a polyolefin composition was prepared, which solved the problem of preparing ultra-high voltage cable insulating materials, achieved insulation performance and stability that meet high voltage levels, and reduced Cost and degassing time.
Patent Information
- Application Number
- CN202411585514.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2024-12-31
AI Technical Summary
It is difficult to prepare ultra-high voltage cable insulating materials that meet the high voltage level of 220kV or above in the prior art, resulting in a high risk of breakdown failure of the cable insulating layer and lack of special polyolefin materials for integrated preparation.
A polyolefin composition is adopted, including 80-90 parts of low-density polyethylene, 0.05-0.4 parts of antioxidant and 0.5-2.5 parts of crosslinking agent, and the ester comonomer and esters are introduced during the polymerization process. Polymer-like is prepared by high-pressure tube polymerization process, combining kneading and post-absorbing crosslinking steps to optimize material performance.
It reduces the amount of polymer surface precipitation, reduces the amount of crosslinking agent used, improves the flexibility and mechanical properties of the material, meets the insulation performance requirements of high voltage grades, extends the degassing time, and reduces production costs.
Smart Images

Figure BDA0005124190380000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polyolefins, and in particular to a polyolefin composition and a preparation method and application thereof. Background Art
[0002] Ultra-pure insulating materials are an indispensable part of high-voltage cables. At present, due to the low voltage level in the field of medium and low voltage cable insulation materials below 35kV in my country, ordinary LDPE can be used in 35kV cables after improvement. However, there is still no breakthrough in ultra-high voltage cable insulation materials of 220kV and above, resulting in a high risk of breakdown failure of the cable insulation layer, which needs to be solved urgently.
[0003] As for the above difficulties, domestic and foreign companies have conducted a lot of research and development. However, since the production and preparation of ultra-high voltage cable materials requires upstream and downstream integration, there is no special polyolefin material in China that can be produced in an integrated manner and meet higher voltage levels of 220kV and above. Summary of the invention
[0004] The purpose of the present invention is to provide a polyolefin composition, a preparation method and application thereof in the sheath of power cables of 110 kV and above.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0006] In a first aspect, the present invention provides a polyolefin composition, which comprises, by weight:
[0007] 1) Polyethylene, 80-90 parts;
[0008] 2) Antioxidant, 0.05-0.4 parts;
[0009] 3) Cross-linking agent, 0.5-2.5 parts.
[0010] Preferably, the polyethylene described in the present invention is low-density polyethylene, which can be a commercially available LDPE product or can be prepared by polymerization.
[0011] Preferably, the polyethylene melt index of the present invention is 1.6-2.4 g / 10 min, and the test conditions are 190°C, 2.16 kg; more preferably, the density of the polyethylene is 0.920-0.924 g / cm 3 .
[0012] Preferably, the polyolefin composition comprises 80-90 parts of polyethylene, for example, 80 parts, 82 parts, 85 parts, 87 parts, 88 parts, 89 parts, 90 parts.
[0013] Preferably, the polyolefin composition comprises 0.05-0.4 parts of antioxidant, for example, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, etc.
[0014] Preferably, the antioxidant is a hindered phenol antioxidant, preferably one or more of Antioxidant 1010, Antioxidant 1098, Antioxidant 300, and Antioxidant 245; more preferably Antioxidant 300.
[0015] Preferably, the polyolefin composition comprises 0.5-2.5 parts of a crosslinking agent, for example, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, etc.
[0016] Preferably, the crosslinking agent is an organic peroxide, preferably one or more of dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxyisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; more preferably dicumyl peroxide.
[0017] The polyolefin composition of the present invention contains ester monomers, which are introduced into the polyolefin composition in the form of blending or copolymerization;
[0018] In a specific embodiment of the present invention, the polyethylene is a product of the polymerization reaction of ethylene and an ester comonomer.
[0019] In a specific embodiment of the present invention, the polymerization reaction is specifically: ethylene, an initiator, a molecular weight regulator (CTA) and an ester comonomer are mixed to carry out a polymerization reaction.
[0020] Preferably, the ester comonomer is diallyl maleate or an acrylate monomer;
[0021] Preferably, the acrylic acid ester monomer is selected from one or more of butyl acrylate, ethyl acrylate and methyl acrylate, more preferably, selected from butyl acrylate.
[0022] Preferably, the amount of the ester comonomer is 0.05%-5% by weight of ethylene, for example, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%,
[0023] 3.5wt%, 4wt%, 4.5wt%, 5wt%, etc.; preferably, the amount of ester comonomer is 0.05-1wt% based on the mass of ethylene.
[0024] Preferably, the molecular weight regulator is selected from conventional molecular weight regulators, such as one or more of propylene, butene, isobutane, n-butane, acetone, propionaldehyde, etc.; the amount of the molecular weight regulator (CTA) is 0.05-1% of the mass of ethylene, such as 0.05%, 0.1%, 0.2%, 0.5%, 0.7%, 0.8%, 1%;
[0025] Preferably, the initiator is selected from peroxide initiators, including but not limited to dicumyl peroxide, di-tert-butyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-pivalate, tert-butyl peroxy-3,5,5-trimethylhexanoate, di-2,5-tert-butyl peroxide, etc. One or more; the amount of the initiator is 0.01%-0.7% of the mass of ethylene, such as 0.01%, 0.03%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, and most preferably 0.01-0.3wt%;
[0026] Preferably, the polymerization reaction adopts a high-pressure tubular polymerization process, and the reactor can be a tubular reactor.
[0027] Preferably, the tubular reactor may be a single-zone tubular reactor or a multi-zone tubular reactor.
[0028] In a preferred embodiment, the tubular reactor is a multi-zone tubular reactor, and the addition points of the initiator, CTA, ethylene, etc. can be controlled to obtain the target polyethylene.
[0029] Preferably, the polymerization reaction pressure is 1800-2700 bar and the temperature is 250-300°C;
[0030] In another specific embodiment of the present invention, the polyolefin composition of the present invention further comprises 0.05-10 parts, such as 0.05 parts, 0.1 parts, 0.5 parts, 1 parts, 3 parts, 5 parts, 8 parts, 10 parts, preferably 0.5-7 parts of ester polymer.
[0031] Preferably, the ester polymer is selected from one or more of ethylene-acrylate copolymer and maleic anhydride grafted polymer.
[0032] Preferably, the ethylene-acrylate copolymer is selected from one or more of ethylene / methyl acrylate copolymer, ethylene / ethyl acrylate copolymer, and ethylene / butyl acrylate copolymer, and more preferably, the ethylene-acrylate copolymer has a melt index of 1-10 g / 10 min, 190° C., 2.16 kg;
[0033] Preferably, the ethylene-acrylate copolymer comprises 15-40 wt%, preferably 18-35 wt% of acrylate comonomer.
[0034] Preferably, the maleic anhydride grafted polymer is a maleic anhydride grafted EBA polymer, and the preferred grafting rate is 1-5 wt%.
[0035] The applicant has found that by adding ester comonomers during the polyethylene polymerization process and / or adding ester polymers during the preparation of the polymer composition, the prepared polyolefin composition can greatly reduce the amount of precipitation on the surface of the polymer composition, and to a certain extent can reduce the amount of cross-linking agent added and shorten the degassing time.
[0036] Preferably, the amount of the crosslinking agent in the polyolefin composition of the present invention is preferably 0.5-2.0 parts, more preferably 0.5-1.8 parts, and further preferably 0.5-1.5 parts.
[0037] The second aspect of the present invention provides a method for preparing the above-mentioned polyolefin composition, and the specific steps include: mixing polyethylene with the antioxidant, the cross-linking agent and other optional auxiliary agents, first mixing and granulating through a reciprocating single-screw extruder or a twin-screw extruder, and post-absorption cross-linking the obtained particles to obtain the polyolefin composition.
[0038] Preferably, the optional other additives can be selected from stabilizers, plasticizers, pigments, flame retardants, antistatic agents, etc. Those skilled in the art can adjust the type and amount of additives added according to actual needs.
[0039] In a preferred embodiment, the other optional auxiliary agents further include the aforementioned ester polymer.
[0040] Preferably, in the method for preparing the polyolefin composition, the mixing temperature is 110-190°C, preferably 120-180°C;
[0041] Preferably, the post-absorption cross-linking temperature is 40-100°C, preferably 50-80°C; the post-absorption time is 6-48h, preferably 8-24h.
[0042] The third aspect of the present invention provides the use of the above-mentioned polyolefin composition in high-voltage insulated cables or ultra-high-voltage insulated cables, such as 35kV and above cables, preferably 110kV and above cables, and more preferably 220kV and above cables.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The present invention introduces ester comonomers during ethylene polymerization and / or adds ester polymers during the modification process. On the premise of ensuring the insulation performance of the material, on the one hand, the surface precipitation amount of the prepared polyolefin composition is reduced to ensure the safety and stability of the long-term operation of the cable. On the other hand, the amount of the crosslinking agent can be reduced, the degassing time is improved, and the cost is reduced. At the same time, the elongation at break, thermal elongation, etc. of the polyolefin composition prepared by the present invention still remain in a relatively good state, and have good flexibility and mechanical properties, realizing the integrated preparation of a special polyolefin material that meets the high voltage level. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited to the enumerated embodiments, but also includes any other known changes within the scope of the claims of the present invention.
[0046] Main raw material sources of embodiments:
[0047] Polyethylene: commercially available, BASF-YPC 2220H;
[0048] Cross-linking agent: dicumyl peroxide DCP, Arkema, purity 99.0%;
[0049] Antioxidant: Antioxidant 300, SI Group, purity 99.0%;
[0050] Butyl acrylate: Wanhua Chemical, purity 99.5%;
[0051] Diallyl maleate: Kanos Company, purity 99.0%;
[0052] EBA: Dow 3717, melt index 7g / 10min, 190℃, 2.16kg;
[0053] EBA: Dow 3117, melt index 1.5g / min, 190℃, 2.16kg;
[0054] Maleic anhydride grafted EBA: Lucobi 1492MHG, grafting rate 1-5wt%;
[0055] Peroxide initiator: tert-butyl peroxy-3,5,5-trimethylhexanoate, di-2,5-tert-butyl peroxide, purity 99.99%; the solvent is isododecane, which is commonly available on the market.
[0056] Other materials are commercially available unless otherwise specified.
[0057] The blended materials prepared in the following examples were tested for anti-aging properties, thermal elongation properties, mechanical properties, electrical properties, and anti-scorch properties.
[0058] Mechanical properties: A tensile machine (INSTRON 5966) was used to test the mechanical properties of the samples. The specimen preparation method was the molding method. The specific test conditions were in accordance with the standard GB / T1040.2-2022.
[0059] Anti-scorch performance: tested by rotorless rheometer (Alpha, MDR), the test temperature is 160°C, the oscillation angle is 0.5°, and the result is expressed by the scorch time TS1.
[0060] Thermal elongation performance: The test is carried out by combined equipment in an oven at a test temperature of 200°C and a test time of 15 minutes.
[0061] Breakdown strength: The breakdown strength tester of Hafele is used, and the specific test standard is in accordance with GB / T1408.1-2016.
[0062] Surface residue: alcohol washing measurement method is adopted, which is carried out in accordance with Q / GDW 11883.1-2018.
[0063] Example 1
[0064] A high-pressure tubular polymerization reactor is used, with a total of four reaction zones. A compressor is used to add 35 t / h of ethylene raw material and 90 kg / h of molecular regulator propylene into the first zone of the reactor when the pressure rises to 1800 bar and the temperature is 180°C. The comonomer butyl acrylate is added into the first zone of the reactor at an amount of 40 kg / h. Initiators tert-butyl peroxypivalate and di-2,5-tert-butyl peroxide are added to isododecane and mixed with it. The total amount of initiator accounts for 0.1 wt% of the amount of ethylene used. The mass ratio of initiator to isododecane is 1:4. They are added to the four reaction zones respectively. The molar ratios of the two initiators in the four reaction zones are 3:1, 1:2, 1:2 and 1:2 respectively, thereby initiating the polymerization reaction. The peak temperature of the reaction is controlled at 260°C-270°C to obtain low-density polyethylene with a density of 0.9204 g / cm 3 , the melt index is 1.99g / 10min.
[0065] Example 2
[0066] A high-pressure tubular polymerization reactor is used, with a total of four reaction zones. A compressor is used to add 35 t / h of refined ethylene raw material and 58 kg / h of propylene into the first zone of the reactor when the pressure rises to 2500 bar and the temperature is 180°C. The comonomer butyl acrylate is added into the first zone of the reactor at an amount of 70 kg / h. The initiators tert-butyl peroxypivalate and di-2,5-tert-butyl peroxide are added to isododecane and mixed with it. The total amount of initiator accounts for 0.1 wt% of the amount of ethylene used. The mass ratio of the initiator to isododecane is 1:4. The initiators are added to the four reaction zones respectively. The molar ratios of the two initiators in the four reaction zones are 3:1, 1:2, 1:2 and 1:2 respectively, thereby initiating the polymerization reaction. The peak temperature of the reaction is controlled at 260°C-270°C to obtain low-density polyethylene with a density of 0.9201 g / cm 3 , the melt index is 1.97g / 10min.
[0067] Example 3
[0068] A high-pressure tubular polymerization reactor is used, with a total of four reaction zones. The ethylene raw material is added to the reactor zone 1 at an amount of 35 t / h and propylene is added to the reactor zone 1 at a pressure of 2500 bar and a temperature of 180°C by a compressor. The copolymerization monomer diallyl maleate is added to the reactor zone 1 at an amount of 35 kg / h. The initiator tert-butyl peroxypivalate and di-2,5-tert-butyl peroxide are added to isododecane and mixed with it. The total amount of initiator accounts for 0.1wt% of the amount of ethylene used. The mass ratio of the initiator to isododecane is 1:4. They are added to the four reaction zones respectively. The molar ratios of the two initiators in the four reaction zones are 3:1, 1:2, 1:2 and 1:2 respectively, thereby initiating the polymerization reaction. The reaction peak temperature is controlled at 260°C-270°C to obtain low-density polyethylene with a density of 0.9205 g / cm 3 , the melt index is 2.02g / 10min.
[0069] Example 4
[0070] A high-pressure tubular polymerization reactor is used, with a total of four reaction zones. The ethylene raw material is added at a flow rate of 35 t / h and the propylene is added at a flow rate of 58 kg / h by a compressor. When the pressure rises to 2500 bar and the temperature is 180°C, the reactor zone 1 is added. The copolymerization monomer diallyl maleate is added at a flow rate of 72 kg / h to the reactor zone 1. The initiator tert-butyl peroxypivalate and di-2,5-tert-butyl peroxide are added to isododecane and mixed with it. The total amount of initiator accounts for 0.1wt% of the amount of ethylene used. The mass ratio of the initiator to isododecane is 1:4. They are added to the four reaction zones respectively. The molar ratios of the two initiators in the four reaction zones are 3:1, 1:2, 1:2 and 1:2 respectively, thereby initiating the polymerization reaction. The peak temperature of the reaction is controlled at 260°C-270°C to obtain low-density polyethylene with a density of 0.9204 g / cm3 , the melt index is 2.06g / 10min.
[0071] Example 5
[0072] Preparation of polymer composition:
[0073] 90 parts of LDPE prepared in Example 1 and 0.18 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.8 parts of crosslinking agent DCP was added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0074] The prepared samples were subjected to relevant performance tests.
[0075] Example 6
[0076] Preparation of polymer composition:
[0077] 90 parts of LDPE prepared in Example 2 and 0.2 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.8 parts of crosslinking agent DCP was added, the post-absorption temperature was 70° C., and the time was 16 hours to obtain a polymer composition sample.
[0078] The prepared samples were subjected to relevant performance tests.
[0079] Example 7
[0080] Preparation of polymer composition:
[0081] 90 parts of LDPE prepared in Example 3 and 0.18 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.45 parts of crosslinking agent DCP was added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0082] The prepared samples were subjected to relevant performance tests.
[0083] Example 8
[0084] Preparation of polymer composition:
[0085] 90 parts of LDPE prepared in Example 4 and 0.18 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.2 parts of crosslinking agent DCP was added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0086] The prepared samples were subjected to relevant performance tests.
[0087] Example 9
[0088] Preparation of polymer composition:
[0089] 80 parts of LDPE prepared in Example 4 and 0.14 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, and 0.9 parts of crosslinking agent DCP was added, the post-absorption temperature was 68° C., and the time was 24 hours to obtain a polymer composition sample.
[0090] The prepared samples were subjected to relevant performance tests.
[0091] Example 10
[0092] Preparation of polymer composition:
[0093] Accurately weigh 90 parts of LDPE 2220H, 0.18 parts of antioxidant 300, and 7 parts of EBA 3717, and mix and extrude the above composition in a reciprocating single-screw extruder at an extrusion temperature of 120-150-180° C. After granulation, enter the drum for post-absorption, add 1.8 parts of crosslinking agent DCP, the post-absorption temperature is 80° C., and the time is 16 hours to obtain a polymer composition sample.
[0094] The prepared samples were subjected to relevant performance tests.
[0095] Embodiment 11
[0096] Preparation of polymer composition:
[0097] 90 parts of LDPE prepared in Example 4, 0.18 parts of antioxidant 300, and 7 parts of maleic anhydride grafted EBA1492MHG were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, and 1.8 parts of crosslinking agent DCP were added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0098] The prepared samples were subjected to relevant performance tests.
[0099] Example 12
[0100] Preparation of polymer composition:
[0101] 90 parts of LDPE prepared in Example 4, 0.18 parts of antioxidant 300, and 4 parts of EBA 3117 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.8 parts of crosslinking agent DCP was added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0102] The prepared samples were subjected to relevant performance tests.
[0103] Comparative Example 1
[0104] A high-pressure tubular polymerization reactor is used. A compressor is used to add ethylene raw materials at a flow rate of 35 t / h and propylene at a flow rate of 58 kg / h. When the pressure rises to 2500 bar and the temperature is 180°C, the reactor is added to the first zone. Initiators tert-butyl peroxypivalate and di-2,5-tert-butyl peroxide are added to isododecane and mixed with it. The total amount of initiator accounts for 0.1wt% of the amount of ethylene used. The mass ratio of the initiator to isododecane is 1:4. The initiators are added to four reaction zones respectively. The molar ratios of the two initiators in the four reaction zones are 3:1, 1:2, 1:2 and 1:2 respectively, thereby initiating the polymerization reaction. The peak temperature of the reaction is controlled at 260°C-270°C to obtain low-density polyethylene with a density of 0.9198 g / cm 3 , the melt index is 2.11g / 10min.
[0105] Comparative Example 2
[0106] A high-pressure tubular polymerization reactor is used. A compressor is used to add ethylene raw material at a flow rate of 35 t / h and propylene at an amount of 58 kg / h. When the pressure is raised to 2500 bar and the temperature is 180°C, the ethylene raw material is added to the first zone of the reactor at a flow rate of 35 t / h and the propylene is added at an amount of 58 kg / h. The comonomer myrcene is added to the first zone of the reactor at an amount of 35 kg / h. Initiators tert-butyl peroxypivalate and di-2,5-tert-butyl peroxide are added to isododecane and mixed with the initiators. The total amount of initiators accounts for 0.1 wt% of the amount of ethylene used. The mass ratio of the initiator to isododecane is 1:4. The initiators are added to four reaction zones respectively. The molar ratios of the two initiators in the four reaction zones are 3:1, 1:2, 1:2 and 1:2 respectively, thereby initiating a polymerization reaction. The reaction peak temperature is controlled at 260°C-270°C to obtain low-density polyethylene with a density of 0.9194 g / cm 3 , the melt index is 2.16g / 10min.
[0107] Comparative Example 3
[0108] Preparation of polymer composition:
[0109] 90 parts of LDPE prepared in Comparative Example 1 and 0.18 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.8 parts of crosslinking agent DCP was added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0110] The prepared samples were subjected to relevant performance tests.
[0111] Comparative Example 4
[0112] Preparation of polymer composition:
[0113] 90 parts of LDPE prepared in Comparative Example 2 and 0.18 parts of antioxidant 300 were accurately weighed, and the above composition was mixed and extruded in a reciprocating single screw extruder at an extrusion temperature of 120-150-180° C. After granulation, it was put into a rotary drum for post-absorption, 1.8 parts of crosslinking agent DCP was added, the post-absorption temperature was 80° C., and the time was 16 hours to obtain a polymer composition sample.
[0114] The prepared samples were subjected to relevant performance tests and the following table was obtained.
[0115]
[0116] By comparing the performance data of different samples in the above table, it can be found that the solution provided by the present invention can significantly reduce the surface residue, which is more conducive to the stability of cable extrusion. At the same time, the mechanical properties, elongation at break, thermal elongation and anti-puncture performance are still very excellent.
[0117] At the same time, it can be found from Examples 7, 8, and 9 that while reducing the amount of cross-linking agent used, the mechanical properties and anti-puncture properties of the samples prepared by the present invention are still relatively good, and since the amount of cross-linking agent used is reduced, the scorch time TS1 can be extended, which is very beneficial for the later degassing.
[0118] The above embodiments are only used to describe the preferred implementation modes of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that various modifications and improvements made by modifying or equivalently replacing the technical solutions of the present invention should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A polyolefin composition, characterized in that In parts by weight, the composition comprises: Polyethylene, 80-90 parts; Antioxidant, 0.05-0.4 parts; Cross-linking agent, 0.5-2.5 parts; Wherein, the composition satisfies at least one of the following conditions: A: The polyethylene contains an ester comonomer; B: The composition further comprises 0.05-10 parts, preferably 0.5-7 parts, of an ester polymer; the ester polymer is an ethylene-acrylate copolymer or a maleic anhydride grafted polymer.
2. The composition according to claim 1, characterized in that The polyethylene is low-density polyethylene with a melt index of 1.6-2.4 g / 10 min and a test condition of 190° C. and 2.16 kg. More preferably, the density of the polyethylene is 0.920-0.924 g / cm 3 .
3. The composition according to claim 1, characterized in that The ester copolymer monomer is diallyl maleate or an acrylate monomer; the acrylate monomer is preferably one or more of butyl acrylate, ethyl acrylate, and methyl acrylate.
4. The composition according to any one of claims 1 to 3, characterized in that The polyethylene is obtained by polymerization reaction of ethylene, an initiator, a molecular weight regulator and an ester comonomer; preferably, the amount of the ester comonomer accounts for 0.05%-5% of the mass of ethylene, more preferably 0.05-1%.
5. The composition according to claim 4, characterized in that The initiator is one or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-pivalate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and di-2,5-tert-butyl peroxide, and the amount of the initiator is 0.01-0.7% of the mass of ethylene, preferably 0.01-0.3%; the molecular weight regulator is preferably one or more of propylene, butylene, isobutane, n-butane, acetone, and propionaldehyde, and the amount of the molecular weight regulator is 0.05-1% of the mass of ethylene; preferably, the pressure of the polymerization reaction is 1800-2700 bar, and the temperature is 250-300° C.
6. The composition according to claim 1, characterized in that The ethylene-acrylate copolymer is selected from one or more of ethylene / methyl acrylate copolymer, ethylene / ethyl acrylate copolymer, and ethylene / butyl acrylate copolymer. Preferably, the ethylene-acrylate copolymer has a melt index of 1-10 g / 10 min, 190° C., and 2.16 kg.
7. The composition according to claim 1, characterized in that The maleic anhydride grafted polymer is a maleic anhydride grafted EBA polymer, and the grafting rate is preferably 1-5 wt%.
8. The composition according to any one of claims 1 to 7, characterized in that The antioxidant is a hindered phenol antioxidant, preferably one or more of antioxidant 1010, antioxidant 1098, antioxidant 300, and antioxidant 245; the crosslinking agent is an organic peroxide, preferably one or more of dicumyl peroxide, dibenzoyl peroxide, di-tert-butyl peroxyisopropylbenzene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, more preferably dicumyl peroxide; the amount of the crosslinking agent is preferably 0.5wt%-2.0wt%, more preferably 0.5wt%-1.8wt%, and even more preferably 0.5wt%-1.5wt%.
9. A method for preparing a polyolefin composition as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing polyethylene, an antioxidant, a crosslinking agent and other optional additives, kneading, granulating, and post-absorption crosslinking to obtain the polyolefin composition; preferably, the kneading temperature is 110-190°C, preferably 120-180°C; preferably, the post-absorption temperature is 40-100°C, preferably 50-80°C; and the post-absorption time is 6-48h, preferably 8-24h.
10. Use of the polyolefin composition prepared by the preparation method according to claim 9 in the field of 35 kV and above cables, preferably 110 kV and above cables, more preferably 220 kV and above cables.
Citation Information
Patent Citations
Shield material used for cable with direct current of 500 kV and below as well as production method thereof
CN107488295A
Direct-current cable insulation material for suppressing space charge and preparation method of direct-current cable insulation material
CN109942933A
Composition with balance of dissipation factor and additive acceptance
CN109963902A
Composite material for shielding direct-current / alternating-current high-voltage cable and preparation method thereof
CN115403853A
Water-resistant tree type overhead material as well as preparation method and application thereof
CN116023727A
